Legal Review of Election Money Politics In Indonesia - Hartana; Didik Suhariyanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Money politics has long been a major concern in the context of general elections in Indonesia. From a legal perspective, the practice of money politics has serious implications for the integrity and fairness of the electoral process. Through a comprehensive legal review, this article investigates the legal framework governing money politics in the 2024 Indonesian elections. By analyzing existing regulations, implementation challenges, and law enforcement efforts, this article presents a clear picture of the status of money politics in the Indonesian legal system. The conclusion highlights the importance of proactive measures to strengthen law enforcement, raise public awareness, and improve the electoral system to maintain integrity and fairness in future elections.